Parents' information needs and their recommendations for effective sexuality education to children - Punjani, Neelam; Scott, Shannon D.; Hussain, Amber (Frontiers in Public Health, 2025)
BackgroundAs children undergo significant developmental transitions, comprehensive sexuality education (CSE) becomes essential. Despite global evidence supporting early CSE, many parents feel underprepared to address topics such as puberty, consent, gender identity, and digital safety with their children. This study explores parents' information needs, barriers, and recommendations for effective sexuality education tools.MethodsA community-based participatory research (CBPR) approach guided six focus group discussions (FGDs) with 30 diverse Canadian parents of children aged 0–18 years, conducted between January 2023 and March 2023. Discussions were audio-recorded, transcribed, and thematically analyzed using Braun and Clarke's inductive approach. Themes were validated through member checking and dual independent coding using NVivo.ResultsThree major themes emerged from the data. First, parents expressed strong need for sexual health education support, including a desire for age-appropriate, inclusive, and culturally relevant resources, along with improved access to trustworthy information. Many felt underprepared to initiate conversations and called for clear guidance tailored to children's developmental stages. Second, parents prioritized a range of core content areas, such as puberty, hygiene, consent, healthy relationships, gender identity, and digital safety and highlighted the emotional and practical challenges of addressing these topics confidently. Third, parents recommended diverse, user-friendly formats for delivering sexual health education, including short digital videos, searchable websites, visual tools like charts and infographics, storybooks, multilingual materials, and structured workshops for both parents and children. Across all groups, there was a shared call for practical tools that are timely, culturally attuned, and capable of supporting value-aligned, ongoing conversations in the home.ConclusionCanadian parents face different barriers to delivering effective sexuality education, shaped by cultural norms, informational gaps, and discomfort with sensitive topics. To empower parents as primary educators, there is a critical need for co-designed, accessible, and culturally inclusive resources that reflect diverse parenting contexts. Future efforts should explore how policy-level interventions particularly within education systems can support these collaborative efforts among families, schools, and healthcare providers to promote informed, age-appropriate, and inclusive sexual development.